DETERMINATION OF ONLINE LEARNING WITH IT AVAILABILITY AS MODERATING VARIABLE - Afridah , Naylatul; Prasojo , Bayu Hari; Biduri , Sarwendah (International Journal Multidisciplinary (IJMI), 2024)
This study aims to examine the effect of hybrid learning implementation, attitudes and acceptance behavior of accounting study students on online learning with introductory accounting courses supported by the availability of technology carried out during the covid-19 pandemic. This research method used a quantitative approach with primary data obtained through data collection techniques for distributing questionnaires to a sample of students. The data was tested using the SEMPLS 3.0 application. The results showed that the implementation of hybrid learning had an effect on online learning in introductory accounting courses, which was supported by the availability of technology. However, the results of the research on the attitude and acceptance behavior of accounting study program students did not affect online learning in introductory accounting courses which were supported by the availability of technology.